Anesthesia for lower extremity vascular bypass with peripheral nerve block - Guimarães,Jordana de Fraga (2017)
Abstract Vascular bypass is a surgical procedure widely used to treat peripheral vascular disease. The intraoperative anesthetic technique and the most appropriate postoperative analgesia for these high-risk patients remain controversial. We present the case of a patient undergoing femoropopliteal-distal bypass in our service, presenting with relevant comorbidities to the choice of anesthetic technique. This patient had several determining factors of difficult airway, especially thoracic kyphoscoliosis, which prevented him from being properly positioned for airway management, and chronic lung disease. This patient was also taken antiplatelet drugs, which is a contraindication for neuraxial block. So, we chose the anesthetic technique of peripheral nerve block, specifically the blockade of femoral and sciatic nerves.